Impact of Managerial Entrenchment on Corporate Social Responsibility: The Moderating Role of Political Embeddedness and Board Independence - Mah-a-Mobeen Ahmed; Mohti, Wahbeeah (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This paper aims to examine how the political effectiveness and board independence moderate the effect of managerial entrenchment on corporate social responsibility (CSR). Design/Methodology/Approach: Data of non-financial firms from the BRIC countries for the period of 2010-2018 were obtained from Thomson Reuters (asset 4) and financial reports. Panel regression model was employed to analyse the data. Research findings: The results show that there is a positive relationship between managerial entrenchment and CSR. Political embeddedness was found to strengthen the positive relationship between managerial entrenchment and CSR. Independent directors was reported to weaken the relationship between managerial entrenchment and CSR. Theoretical contribution/Originality: Theoretically, this study contributes to the literature on agency theory. The finding provides novel insights into how managerial entrenchment affects CSR activities. It also expands the body of knowledge on corporate governance and CSR by focusing on manager’s self-interest to shareholder’s interest. Practitioner/Policy implication: Practically, this study provides valuable information to stakeholders, regulatory authorities and investors who wish to assess various antecedents of CSR. Research limitation/Implications: Future study should consider comparing the developed and developing countries. Other aspects of CSR should also be considered for better understanding. This study sheds light on the relevance of promoting the social and environmental awareness mechanisms surrounding companies in addition to developing CSR policies focused on corporations of BRIC countries. Keywords: Corporate Social Responsibility, Managerial Entrenchment, Political Embeddedness, Board Independence, Agency Theory JEL Classification: G02, G11